Photography as Social Transformation - Frąckowiak, Maciej, author.
1 online resource (236 pages)
Keywords: Photography as Social Transformation resituates the practices of photography within contemporary sociological thinking. It examines how photography influences and shapes social order in the social media age and offers a methodological framework for studying transformation, revealing the forms the process can take and the settings in which it occurs.Photography and the transformation it effects is conceptualised using actor-network theory, allowing it to be effectively studied in the context of globalisation and the rapid spread of mobile devices. Going beyond consideration of the images themselves, Maciej Frąckowiak analyses the rituals and devices used to take them, the networks in which they circulate, conversations about them, and institutional attempts to regulate their content. More than 'dead paper' or a digital file or a visual representation, Photography as Social Transformation shows how photography is a complex social phenomenon, causal and capable of producing change.Offering case studies from around the world and drawing on a range of sources, giving priority to media coverage from specialised and popular venues, Photography as Social Transformation is for students and scholars of the sociology of media, visual sociology, photographic methods in research, media and communications, cultural studies, and photography theory.